2017
DOI: 10.31631/2073-3046-2017-16-1-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Influenza Surveillance System in the Russian Federation: the Main Results of the Sentinel Surveillance for Influenza and other Acute Respiratory Viral Infections

Abstract: Existing influenza surveillance system is constantly improved to obtain comprehensive information for understanding of continuously changing situation with the influenza, which is a consequence of the highest variability of the pathogen, its ability to reassortment and the imminence of emergence a new shift-variants of the virus that could cause the next pandemic events. For this purpose, since the 2010 - 2011 epidemic season, in addition to the traditional surveillance system (TS) a new well standardized sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
1
0
3
Order By: Relevance
“…This may be due to hospitalization of pregnant women of childbearing age, among which influenza A(H3N2) was detected 1.5 times more often, compared to the adjusted control group. These results are consistent with data obtained in sentinel surveillance indicating that pregnancy is one of the leading risk factors for hospitalization with influenza [16]. The most significant SARI agents in ICU were RSV, influenza A(H1N1)pdm09 virus, and rhinovirus (28.1%, 9.2%, and 8.2%, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be due to hospitalization of pregnant women of childbearing age, among which influenza A(H3N2) was detected 1.5 times more often, compared to the adjusted control group. These results are consistent with data obtained in sentinel surveillance indicating that pregnancy is one of the leading risk factors for hospitalization with influenza [16]. The most significant SARI agents in ICU were RSV, influenza A(H1N1)pdm09 virus, and rhinovirus (28.1%, 9.2%, and 8.2%, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Other respiratory viruses were less often causative agents of SARI. 2.9 0.0 4.9 1.9 3.9 0.0 2.9 16 Analysis of age-related etiology of SARI in the ICU showed that the percent of influenza cases increased with age from 21% in young patients (0-2 years) to 40% in school children. In contrast, the ORV impact decreased from 64% to 20%.…”
Section: Burden Of Influenza and Orvmentioning
confidence: 99%
“…Организационная структура традиционного надзора (ТН) и сигнального надзора (СН) за гриппом и другими респираторными инфекциями в России была описана ранее [1,5,19]. ТН осуществлялся силами двух Национальных центров по гриппу ВОЗ (НЦГ) в Санкт-Петербурге и Москве в сотрудничестве с 60 региональными базовыми лабораториями (РБЛ) в системе Роспотребнадзора, СН за ТОРИ и ГПЗ/ОРИ -в 10 РБЛ расположенных в разных федеральных округах (ФО) России.…”
Section: материалы и методыunclassified
“…В Российской Федерации одним из направлений оптимизации системы эпидемиологического надзора за гриппом и ОРВИ стало внедрение в 2009 г. системы сигнального надзора в рамках Глобальной системы надзора за гриппом (GISRS). Задачами этой системы стали выявление и регистрация случаев ТОРИ, анализ их этиологии, клинико-эпидемиологических особенностей и факторов риска развития [7][8][9][10][11].…”
Section: Introductionunclassified
“…В настоящее время в России в системе сигнального надзора работают 10 регионов страны. Многолетние данные показали, что результаты сигнального надзора значительно дополняют традиционную систему надзора и имеют существенную взаимосвязь с данными, полученными в других странах мира [8,10]. В масштабах Уральского региона подобные исследования не проводились.…”
Section: Introductionunclassified